Idiopathic pulmonary fibrosis: from clinical trials to real-life experiences - Sergio Harari; Antonella Caminati (European Respiratory Review, 2015)
Randomised controlled clinical trials are fundamental in medicine to develop new effective drugs and new therapeutic regimens and are the strength of evidence-based medicine. These studies allow us to avoid the repetition of misleading experiences that have been reported in the past, where drugs or associations were utilised without compelling evidence and ultimately proven to be ineffective. In recent years, randomised clinical trials have been conducted and concluded for many rare diseases, including idiopathic pulmonary fibrosis. However, clinical trials do not always reflect the real-life scenario. Patients selected for clinical trials present fewer comorbidities, they fall between certain age limits, and the severity of their disease is defined; therefore, they do not always reflect the whole of the population affected by a specific disease. These are the reasons why we also need data that mirror real-life experience. The limitations that these kind of studies present are always several and the studies should be interpreted with caution, although they can fill the important gap between efficacy and effectiveness. In this article, we will review the existing clinical data on real-life treatment of idiopathic pulmonary fibrosis.